PECULIARITIES OF EARLY TERMINATION OF A SPORTS CONTRACT UNDER THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Sports contracts are becoming key tools in regulating legal relations in professional sports. In other words, sports contracts are an integral part of professional sports, and their conclusion represents an important stage in the careers of all athletes. Nevertheless, as noted by E. T. Musaev, the nature of a sports contract in legal science is poorly studied, that is why research of the legal nature of contracts in sports is relevant and in demand [1, p. 63]. We believe that a correct understanding of the legal essence and features of sports contracts is extremely important, since a lack of awareness in this area can lead to conflict situations and adverse consequences for both athletes and sports organisations.